Community Drivers Affecting Adherence to WHO Guidelines Against COVID-19 Amongst Rural Ugandan Market Vendors - Usman, Ibe Michael; Ssempijja, Fred; Ssebuufu, Robinson; Lemuel, Ann Monima; Archibong, Victor Bassey; Ayikobua, Emmanuel Tiyo; Aruwa, Joshua Ojodale; Kembabazi, Stellamaris; Kegoye, Eric Simidi; Ayuba, John Tabakwot; Okeniran, Olatayo Segun; Echoru, Isaac; et al. (Frontiers in Public Health, 2020)
Background: Market vendors occupy a strategic position in the fight against the spread of SARS CoV-2 in rural Uganda. To successfully contain the spread of the virus, special attention needs to be given to this set of people by assessing the type of information, source of information, and practices they inculcate as regards adherence to WHO guidelines in the fight against COVID-19 in Uganda. The study aimed to assess the role of information sources, education level, and phone internet connectivity in influencing COVID-19 knowledge among the rural market vendors; and the relationship existing between knowledge, attitude, and practices among them. Methods: The study was a descriptive cross-sectional study among rural market vendors (n = 248) in southwestern Uganda. Information was collected using a questionnaire and descriptively presented as frequency and percentages. Results: The study showed that the majority of the rural market vendors had sufficient information regarding COVID-19 with the majority being female individuals and have attained a secondary level of education, The general percentage score for knowledge, attitude, and practices were (75.57, 82.6, and 76.50% respectively). There was a positive correlation between attitude and practices (r = 0.17, p = 0.007), as well as their knowledge with practices (r = 0.29, p < 0.001). The majority of the people in the population did not have their phones connected to the internet (OR = 1.96, 95%CI: 1.16–3.31, P = 0.01). The majority of people received their information regarding COVID-19 from one source (radio) (OR = 1.55). Conclusion: Where and how the rural market vendors get their information and education level are vital in breaking COVID 19 infection circle in line with WHO guidelines. Therefore, sources of information and education level played a key role in molding their knowledge and practices. However, the level of knowledge on COVID 19 among our respondents was not linked with phone internet connectivity.